Genetic Abrogation of Adenosine A3 Receptor Prevents Uninephrectomy and High Salt–Induced Hypertension. Issue 7 (18th July 2016) - Yang, Ting; Zollbrecht, Christa; Winerdal, Malin E.; Zhuge, Zhengbing; Zhang, Xing‐Mei; Terrando, Niccolo; Checa, Antonio; Sällström, Johan; Wheelock, Craig E.; Winqvist, Ola; Harris, Robert A.; Larsson, Erik; et al.
Abstract : Background: Early‐life reduction in nephron number (uninephrectomy [UNX]) and chronic high salt (HS) intake increase the risk of hypertension and chronic kidney disease. Adenosine signaling via its different receptors has been implicated in modulating renal, cardiovascular, and metabolic functions as well as inflammatory processes; however, the specific role of the A3 receptor in cardiovascular diseases is not clear. In this study, gene‐modified mice were used to investigate the hypothesis that lack of A3 signaling prevents the development of hypertension and attenuates renal and cardiovascular injuries following UNX in combination with HS (UNX‐HS) in mice. Methods and Results: Wild‐type (A3 +/+ ) mice subjected to UNX‐HS developed hypertension compared with controls (mean arterial pressure 106±3 versus 82±3 mm Hg; P <0.05) and displayed an impaired metabolic phenotype (eg, increased adiposity, reduced glucose tolerance, hyperinsulinemia). These changes were associated with both cardiac hypertrophy and fibrosis together with renal injuries and proteinuria. All of these pathological hallmarks were significantly attenuated in the A3 −/− mice. Mechanistically, absence of A3 receptors protected from UNX‐HS–associated increase in renal NADPH oxidase activity and Nox2 expression. In addition, circulating cytokines including interleukins 1β, 6, 12, and 10 were increased in A3 +/+ following UNX‐HS, but these cytokines were already elevated in naïve A3 −/− mice and did not change following UNX‐HS. Conclusions: Reduction in nephron number combined with chronic HS intake is associated with oxidative stress, chronic inflammation, and development of hypertension in mice. Absence of adenosine A3 receptor signaling was strongly protective in this novel mouse model of renal and cardiovascular disease.